Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D; Büker, Patrick; Ashmore, Mike R (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata

Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D.; Büker, Patrick; Ashmore, Mike R. (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
The following values have no corresponding Zotero field: accession-num: 17412465
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance